A virtual problem of nineteenth-century culture - Terni, Jennifer (Primerjalna književnost, 2013)
Using Gilles Deleuzes idea of virtualization, this paper argues that realism should be reconsidered as a collective problematization of an ontology of the everyday. It charts an alternative to the pragmatic critique of post-structuralism, taking up the problem of representation, the history of description, aesthetics, scale, modeling and outlines a counter-model to the concept of the social imaginary.
Keywords: Deleuze, Gilles, 1925-1995; filozofija literature; estetska izkušnja; realizem; realistični roman; virtualizacija; poststrukturalizem; književnost; literature